Psychosocial outcomes at three and nine months after good neurological recovery from aneurysmal subarachnoid haemorrhage: predictors and prognosis. Issue 6 (1st June 2002) - Powell, J; Kitchen, N; Heslin, J; Greenwood, R
Abstract : Objectives: To investigate (1) the prevalence of various aspects of cognitive and psychosocial dysfunction, including post-traumatic stress symptoms, over nine months after subarachnoid haemorrhage (SAH); (2) whether SAH is preceded by increased life stress; (3) to what extent adverse outcomes may be predicted from preillness life stress, early neurological impairment, age, and sex; and (4) relations between emotional and functional outcomes. Methods: 52 patients with good neurological recovery after surgery for SAH were each matched for age, sex, and occupation with a healthy control participant. SAH patients were assessed three and nine months postdischarge on measures of cognitive functioning, mood, and social functioning. Objective stressors and subjective life change during the preceding year were rated retrospectively. Controls completed measures of mood and social functioning once only. Results: Compared with controls, SAH patients showed increased mood disturbance, subtle cognitive impairment, and abnormally low independence and participation on measures of social functioning. 60% showed clinically significant post-traumatic stress symptomatology (intrusive thoughts or avoidance of reminders) at three months and 30% at nine months. Independence in activities of daily living was greatly reduced in half to a third of the sample at both three and nine months. Productive employment was below the 10th percentile of the control group for 75% of patients at three months and for 56% at nine months; this outcome could not be predicted from selected demographic, premorbid, or clinical variables but dependence on others for organisational activities was predicted by impaired prose recall. Mood at nine months was strongly predicted by prior mental health problems, poor physical health, dysphasia, and impaired prose recall at three months. There was no evidence of an abnormally high level of stressful life events in the year before SAH, although patients rated their subjective level of stress in this period slightly more highly than did the control participants. Conclusions: These findings highlight the need for structured support and treatment after surgery for SAH to reduce persisting mood disturbance and increase independence and participation.